Novel Insights of Oligometastases and Oligo-Recurrence and Review of the Literature - Yuzuru Niibe; Joe Y. Chang (Pulmonary Medicine)
Oligometastases and oligo-recurrence are among the most important notions of metastatic and recurrent cancer. The concept of oligometastases is related to the notion that cancer patients with 1–5 metastatic or recurrent lesions that could be treated by local therapy achieve long-term survival or cure, while the concept of oligo-recurrence is related to the notion that cancer patients with 1–5 metastatic or recurrent lesions that could be treated by local therapy have controlled primary lesions. Achievement of long-term survival or cure in patients with oligometastases and oligo-recurrence is cancer and organ specific. These facts rely on the seed and soil theory and multiple steps of cancer progression. Oligo-recurrence is considered to have a better prognosis than oligometastases. In patients with oligometastases and oligo-recurrence, the oligometastases and oligo-recurrence are sometimes cured with only local therapy, which is an example of the abscopal effect, previously described in relation to cure of lesions outside of the field of radiation therapy without systemic therapy. Oligometastases and oligo-recurrence can now be cured by less invasive local treatment methods combined with systemic therapy. The mechanisms of oligometastases and oligo-recurrence, as well as novel insights into these important concepts, are presented in this paper.